2013
DOI: 10.2337/db12-1311
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pyruvate Carboxylase Reduces Gluconeogenesis and Adiposity and Improves Insulin Resistance

Abstract: We measured the mRNA and protein expression of the key gluconeogenic enzymes in human liver biopsy specimens and found that only hepatic pyruvate carboxylase protein levels related strongly with glycemia. We assessed the role of pyruvate carboxylase in regulating glucose and lipid metabolism in rats through a loss-of-function approach using a specific antisense oligonucleotide (ASO) to decrease expression predominantly in liver and adipose tissue. Pyruvate carboxylase ASO reduced plasma glucose concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 53 publications
3
102
0
Order By: Relevance
“…Previous reports have shown that ASO treatment can lead to repression of specific gene expression in several tissues in vivo, particularly liver and adipose tissue (Supplemental Figs. S2, S3;Watts et al 2005;Kumashiro et al 2013). …”
Section: Thrap3 Specifically Controls a Diabetic Gene Set In Culturedmentioning
confidence: 99%
“…Previous reports have shown that ASO treatment can lead to repression of specific gene expression in several tissues in vivo, particularly liver and adipose tissue (Supplemental Figs. S2, S3;Watts et al 2005;Kumashiro et al 2013). …”
Section: Thrap3 Specifically Controls a Diabetic Gene Set In Culturedmentioning
confidence: 99%
“…However, the levels of PC and its activity are elevated in livers of type 1 diabetic rats and mice (Wimhurst and Manchester, 1970), and in genetically obese Zucker diabetic fatty rats (Lynch et al, 1992;Jitrapakdee et al, 1998), suggesting that insulin exerts its inhibitory effect on hepatic PC expression. Furthermore, antisense oligonucleotide-mediated suppression of hepatic PC expression in rats fed with normal diet marginally reduced fasting plasma glucose and endogenous glucose production, while this effect was more pronounced in rats fed with high-fat diet, suggesting the critical role of PC in hepatic gluconeogenesis, especially during the development of diabetes (Kumashiro et al, 2013). Recent study has shown that in humans, the level of hepatic PC protein is increased in those who have hyperglycemia, supporting the role of PC being one of the key gluconeogenic enzymes in human (Kumashiro et al, 2013), while this evidence was absent for PEPCK-C and G6Pase (Samuel et al, 2009).…”
Section: Pyruvate Carboxylasementioning
confidence: 91%
“…It has recently been reported that hepatic expression of Pepck and G6pc mRNA was not related to fasting hyperglycemia in humans and in rodent models of T2D [168]. The authors revealed a strong association between pyruvate carboxylase protein expression and glycemia in humans [169]. Pyruvate carboxylase is allosterically activated by acetyl-CoA [170].…”
Section: Chapter V Conclusion and Future Directionsmentioning
confidence: 94%